Instagram Assisted Portfolio Assessment to Improve Students' Creative Thinking Skills - Irkhamni Abdillah; Kartimi Kartimi; Ria Yulia Gloria (Scientiae Educatia: Jurnal Pendidikan Sains, 2021)
The purpose of this study was to find out differences in student activities between those implemented by Instagram-assisted portfolio assessments and those not applied by Instagram-assisted portfolio assessment differences in improving students' creative thinking skills between those implemented by Instagram- assisted portfolio assessment and those not implemented by Instagram-assisted portfolio assessments. They knew students 'responses about applying Instagram-assisted portfolio assessments to improve students' creative thinking skills. The approach in this study uses a quantitative approach with the design pretest-posttest control group. The population in this study were all class X students of SMAN 1 Tanjung, numbering 238 students. Samples taken were two classes, each of which amounted to 34 students. Data collection techniques used are observation sheets, tests, and questionnaires. The study results show that students' activities applied portfolio assessment assisted Instagram with an average of 73% with good criteria while those not applied Instagram-assisted portfolio assessment 58% with sufficient measures. Instagram-assisted portfolio assessment showed an increase in creative thinking skills at experimental class the average N-Gain by 0.60 medium categories. Instagram-assisted portfolio assessment can improve students' creative thinking skills.